PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 009 TANJUNG PENYEMBAL - Jasmida '; Mahmud Alpusari Mahmud Alpusari; Munjiatun ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: The problem in this study is the low learning outcomes SDN 009 Class III Tanjung Penyembal with - average baseline value of 62.14. This study aims to improve science learning outcomes SDN 009 class III Tanjung Penyembal through "Application of Cooperative Learning Model type Number Head Together (NHT)". Data collection instrument in this study was a test of student learning outcomes, teacher observation sheet activities and observations of student activity sheets. This study was conducted in March to April 2014 was done 2 cycles. The subjects were SDN 009 Class III Tanjung Penyembal 28 in total siswa.Aktivitas teacher at the first meeting with the percentage of first cycle 37.5% less category, increased in the second meeting of the first cycle with the percentage of 58.33% categorized enough. Then increased again at the first meeting of the second cycle with the percentage of 70.83% categorized well, and at the second meeting of the second cycle increased 87.5% categorized very well. While the activities of the students at the first meeting of the first cycle with a percentage of 33.33% category to the category of less increased in the second meeting of the first cycle with a percentage of 62.5% categorized enough. In the second cycle the first meeting of the percentage of 75% with both categories have increased at the second meeting of the second cycle with a percentage of 87.5% categorized very well. Average - The average results of the study to increase base score. Value - average score of 62.14 basis increased in the first cycle with value - average 66.96 and the second cycle increased to 83.03. Percentage increase in learning outcomes of basic scores to UH I reached 7.76% and from the base to the UH II scores increased by 28.9%, the percentage of completeness reached 83.33% and otherwise completed. From these results it can be concluded that the application of Cooperative Learning Model Number Type Head Togather (NHT) Hasik can Improve Student Learning IPA SDN 009 III Class Tanjung Penyembal. Keywords : Cooperative Learning Model Type NHT, Learning Outcomes IPA